System of activities involving recreational games for the improvement of english vocabulary - Vera Salas, Alex David; Maza Córdova, José Luis (Machala: Universidad Técnica de Machala, 2023)
The objective of the study presented was the application of a system of activities involving recreational games such as Colour it - Trace it - write it - make it, in order to improve English vocabulary in 7th grade students of the Jaime Roldós Aguilera school. It was developed from a quantitative perspective of experimental type with a population of 35 students of the basic general educational institution Jaime Roldós Aguilera, where were applied the methods of theoretical level such as, systemic method, historica llogical method, systemic analytical, and deductive hypothetical and also the empirical level such as: observation, test and experiment. The application of the pedagogical test allowed measuring the students' general knowledge of English vocabulary, which was insufficient. In order to solve the deficiencies identified in the English vocabulary, a class system was designed and applied based on the use of recreational games. The results obtained were subjected to hypothesis testing by applying inferential statistics with the CHI SQUARE test as a technique that allowed to prove the effectiveness of the system of activities in relation to the increase of the students' English vocabulary
El estudio que se presentó tuvo como objetivo la aplicación de un sistema de actividades que involucre juegos recreativos como Colour it -Trace it - write it - make it, con el fin de mejorar el vocabulario en inglés en los estudiantes del 7mo grado de educación básica de la escuela Jaime Roldós Aguilera. Se desarrolló desde una perspectiva cuantitativa de tipo experimental con una población de 35 estudiantes de la Institución educativa general básica Jaime Roldós Aguilera, en donde fueron aplicados los métodos de nivel teórico tales como: método sistémico, método histórico-lógico, Analítico sistémico, e hipotético deductivo y además del nivel empírico como: la observación, el test y el experimento. La aplicación de la prueba pedagógica permitió medir el conocimiento general del vocabulario del idioma inglés de los estudiantes el cual fue insuficiente. Con el fin de resolver las falencias identificadas en el vocabulario del inglés se diseñó y aplicó un sistema de clases que se apoyó en el uso de juegos recreativos. Los resultados obtenidos fueron sometidos a una comprobación de la hipótesis aplicando la estadística inferencial con la prueba CHI CUADRADO como técnica que permitió comprobar la efectividad del sistema de actividades con relación al incremento del vocabulario del idioma inglés en los estudiantes.
Keywords: VOCABULARIO; JUEGO; SISTEMA; CLASE